2021
DOI: 10.1111/apa.15999
|View full text |Cite
|
Sign up to set email alerts
|

Persistent symptoms in Swedish children after hospitalisation due to COVID‐19

Abstract: COVID-19 is generally mild in children, 1 and post-acute inflammatory conditions that are temporally associated with the virus are rare, but potentially severe. However, some children and adults experience persistent symptoms after COVID-19. 2 Long COVID has not been precisely defined, but one study reported symptoms approximately 60 days after the primary diagnosis. 3 Although adult long COVID is increasingly being studied, the magnitude of persistent symptoms in children remains unclear. This Swedish study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 7 publications
4
86
2
Order By: Relevance
“…In contrast, a cross-sectional observational study from the Netherlands presented alarming data showing that up to 87% of pediatric COVID-19 survivors experienced persistent fatigue (28). Similar data has been reported from Sweden, showing fatigue as the most common symptom in hospitalized children, with a median follow-up time of 219 days (29). Among the adult population, a similar tendency has been observed, with 63% of hospitalized patients reporting persistent fatigue 6 months after acute COVID-19 (30).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast, a cross-sectional observational study from the Netherlands presented alarming data showing that up to 87% of pediatric COVID-19 survivors experienced persistent fatigue (28). Similar data has been reported from Sweden, showing fatigue as the most common symptom in hospitalized children, with a median follow-up time of 219 days (29). Among the adult population, a similar tendency has been observed, with 63% of hospitalized patients reporting persistent fatigue 6 months after acute COVID-19 (30).…”
Section: Discussionmentioning
confidence: 78%
“…Many of the reported long-COVID symptoms are non-specific, thus making it difficult to distinguish long COVID from pandemic-associated symptoms caused by lockdown measures (i.e., restricted socializing, school closures), which have been shown to have negative effects on the well-being and mental health of children and adolescents (16,32,39). In order to prove the correlation between SARS-CoV-2 infection and symptom persistence in children, it is crucial to carry out research with matched control groups and validated research tools, including objective functional testing and imaging, since self-reported symptoms may be difficult to validate (14,16,29).…”
Section: Discussionmentioning
confidence: 99%
“… 40 Furthermore, one study found an association between longer hospitalization and more severe persistent symptoms, and between PIMS-TS and a higher prevalence of persistent symptoms. 38 …”
Section: Results Of Studies Of Long Covid In Children and Adolescentsmentioning
confidence: 99%
“… 10 About the paediatric age, at least 10% of children who test positive for the virus still have persistent symptoms that deserve to be properly assessed. 11 …”
Section: Who Develops Long Covid?mentioning
confidence: 99%